Implementing a digital infrastructure for the lab using a central laboratory server and the SiLA2 communication standard. Issue 3 (9th December 2020) - Porr, Marc; Lange, Ferdinand; Marquard, Daniel; Niemeyer, Laura; Lindner, Patrick; Scheper, Thomas; Beutel, Sascha
Abstract: In this report, a fully integrated solution for laboratory digitization is presented. The approach presents a flexible and complete integration method for the digitally assisted workflow. The worker in the laboratory performs procedures in direct interaction with the digitized infrastructure that guides through the process and aids while performing tasks. The digital transformation of the laboratory starts with standardized integration of both new and "smart" lab devices, as well as legacy devices through a hardware gateway module. The open source Standardization in Lab Automation 2 standard is used for device communication. A central lab server channels all device communication and keeps a database record of every measurement, task and result generated or used in the lab. It acts as a central entry point for process management. This backbone enables a process control system to guide the worker through the lab process and provide additional assistance, like results of automated calculations or safety information. The description of the infrastructure and architecture is followed by a practical example on how to implement a digitized workflow. This approach is highly useful for – but not limited to – the biotechnological laboratory and has the potential to increase productivity in both industry and research for example by enabling automated documentation.